A systematic review of e-wallet usage intention: integrating UTAUT2 with perceived security / Jasmine Vivienne Andrew ... [et al.] - Andrew, Jasmine Vivienne; Ambad, Sylvia @ Nabila Azwa; Wong, Nur Syahidah Abdullah; Nordin, Sakka; Karen, Esther Tan (Universiti Teknologi MARA, Perlis, 2021)
The growth of cashless payment has grown exponentially, including that of e-wallet, in line with the government's plan to build a cashless society. The e-wallet phenomenon is fast becoming an important component for financial inclusion in emerging economies as studies found that the use of digital financial services like mobile money and other fintech applications could provide many potential development benefits. Countries like China have experienced the highest growth in cashless payments over the last five years and is said to be the most educated on mobile payment services. Despite the rapid development of this technology, organizations and consumers are still concerned about rising security issues. As the e-wallets markets are further expected to increase exponentially in Malaysia, it is crucial to study the consumers' behavioral intention to use e-wallets for the benefits of e-wallets service providers and users in Malaysia. Correspondingly, this paper presents a review of the literature aimed at advancing the body of knowledge by proposing a conceptual model on consumers' behavioral intention to use e-wallet (mobile payment) using UTAUT2 as a baseline model. This paper is built upon a systematic literature review method. This paper provides practical implications that would assist e-wallet service providers when devising appropriate strategies in planning and increasing consumers' intention to use the e-wallet.